Bilaterální asymetrická traumatická luxace kyčelních kloubů - Paša, L; Veselý, R; Kelbl, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2017)
The authors present a rare case of bilateral asymmetric traumatic dislocation of hip joints, where the left joint was treated conservatively after the reduction, while the right joint, with an acetabular fragment interposition, was treated surgically - by arthroscopically assisted reduction and fixation of an osteochondral fragment of posterior wall of the acetabulum. The female patient healed with no complications, showing an excellent clinical outcome with no signs of instability or limited mobility of hip joints, and also with no signs of para-articular calcification or necrosis of the hip at 1 year after the injury and treatment. Bilateral asymmetric dislocation of hip joint is a rare injury with the total incidence of 150 cases as reported by the literature. Recently, its incidence is higher due to the increased traffic and the associated accident rate. A precise and prompt reduction of the injured hip joint is always necessary, if possible under general anesthesia. Also, it is always necessary to carry out a complete examination of the patient since this type of injury is always caused by a strong force and is often accompanied by injuries of other parts of the body. Key words: bilateral asymmetric dislocation of hip joints, hip arthroscopy, acetabular fracture.
Keywords: Hip Dislocation; Arthroscopy; Fracture Fixation; lidé; Female; artroskopie; luxace kyčle; výsledek terapie; Treatment Outcome; fixace fraktury; ženské pohlaví; Humans